Breeding patterns of the Great Tit (Parus major) in a pine plantation and a holm oak forest in a Mediterranean region (southern Spain) - Catalan, R M; Haeger, J F (Revue d'Ecologie la Terre et la Vie, 1996)
This study compares breeding patterns of nestbox-breeding Great Tits (Parus major) between two adjacent forest habitats: a pine plantation and a Mediterranean helm oak Quercus rotundifolia forest. Breeding density increased in both forests when nestbox density was raised. The breeding season started earlier in the pinewood, but tended to end at the same time in both habitats. Reproductive effort was higher in the plantation as reflected in egg volume rather than clutch size. Time of season had an effect on clutch size but not on the size of the eggs which remained constant throughout the breeding season. Breeding success was associated with habitat, with both the number of fledglings and their weight being higher in the pinewood. These parameters showed a seasonal trend in the pinewood but not in the helm oak forest. Our results show that Great Tit achieves a higher reproductive performance in the pinewood in spite of its recent settling in this habitat.
APS
Keywords: breeding pattenrns; great tits; Mediterranean; nest-box; Parus major; pine plantation; Quercus ilex